2018
DOI: 10.1016/j.colsurfb.2017.12.044
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol liposomes and lipid nanocarriers: Comparison of characteristics and inducing browning of white adipocytes

Abstract: Trans -resveratrol (R) has a potential to increase energy expenditure via inducing browning in white adipose tissue. However, its low levels of aqueous solubility, stability, and poor bioavailability limit its application. We have successfully synthesized biocompatible, and biodegradable R encapsulated lipid nanocarriers (R-nano), and R encapsulated liposomes (R-lipo). The mean particle size of R-nano and R-lipo were 140 nm and 110 nm, respectively, and their polydispersity index values were less than 0.2. Nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 33 publications
0
43
0
Order By: Relevance
“…68 In fact, this observation has led to a wealth of research focusing on how to increase the bioavailability of this potent anti-inflammatory natural product so that it can be absorbed and circulated to various affected organs, such as by way of encapsulation in nanoparticles or some other vehicle. 69,70 However, our findings suggest that resveratrol alters the microbiome directly and this leads to the anti-inflammatory effects during colitis, even before it becomes bioavailable to various organs after oral consumption.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…68 In fact, this observation has led to a wealth of research focusing on how to increase the bioavailability of this potent anti-inflammatory natural product so that it can be absorbed and circulated to various affected organs, such as by way of encapsulation in nanoparticles or some other vehicle. 69,70 However, our findings suggest that resveratrol alters the microbiome directly and this leads to the anti-inflammatory effects during colitis, even before it becomes bioavailable to various organs after oral consumption.…”
Section: Discussionmentioning
confidence: 75%
“…It is particularly interesting to note that the poor bioavailability of resveratrol during oral consumption, which is attributed to the weak aqueous solubility of the compound, has always been an issue in terms to suggesting this natural product as a treatment of various disease . In fact, this observation has led to a wealth of research focusing on how to increase the bioavailability of this potent anti‐inflammatory natural product so that it can be absorbed and circulated to various affected organs, such as by way of encapsulation in nanoparticles or some other vehicle . However, our findings suggest that resveratrol alters the microbiome directly and this leads to the anti‐inflammatory effects during colitis, even before it becomes bioavailable to various organs after oral consumption.…”
Section: Discussionmentioning
confidence: 84%
“…In addition to all these properties, there are studies showing that when used orally they can also be effective in the wound healing process 20 . However, it has been shown that oral administration of resveratrol has low bioavailability and stability in studies performed 23,24 . Loading of nano-molecules to increase the bioavailability of molecules with these properties in the living system has given a different perspective to current treatment approaches 25 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, the study of Ethemoglu et al 22 investigated the effect of trans-resveratrol loaded in liposomes on penicillin-induced epileptic activity model. When trans-resveratrol is used orally, its effectiveness is limited due to low water solubility, stability, and low bioavailability 23,24 . Nanoencapsulation has proven that molecules are effective in increasing water solubility, chemical stability, and bioavailability of bioactive compounds 25 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, to overcome poor solubility and bioavailability of trans‐resveratrol (R), an antiobesity drug that induces browning in WAT, Zu et al synthesized R encapsulated lipid nanocarriers (R‐nano), and R encapsulated liposomes (R‐lipo). Nanoencapsulation of R‐nano and R‐lipo increased the aqueous solubility and stability of R, as well as the uptake by 3T3‐L1 cells, leading to enhanced browning activities of R and improved efficiency of obesity treatment . However, the therapeutic features as well as molecular mechanisms of R‐nano and R‐lipo should be thoroughly characterized before they are clinically translated to methods of obesity treatment.…”
Section: Nanotechnology As a Treatment For Obesitymentioning
confidence: 99%